Medals of Spanish Masonic exile in Mexico: State of the art - Cuadrado Merchán, Manuel (2021)
Research on the Spanish Masonic exile in Mexico during Franco’s dictatorship has been approached from the historiography in the context of the republican exile. Some historians have studied the institutional links that these freemasons established with Mexican Freemasonry, their integration into the cultural fabric of the host country, their publications, as well as biographies. A field of study that still needs further investigation is the history of the material culture of those Freemasons’ forty years of exile. In this paper, we attempt to establish the state of the art of research of the medals of the Spanish Freemasons in Mexico.